2008
DOI: 10.1111/j.1574-6968.2007.00998.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the potential for dissimilatory ferric iron reduction is widespread among acidophilic heterotrophic bacteria

Abstract: Nineteen characterized strains and isolates of acidophilic heterotrophic bacteria were screened for their abilities to catalyse the reductive dissolution of the ferric iron mineral schwertmannite, under oxygen-limiting conditions. Acidocella facilis, Acidobacterium capsulatum, and all of the Acidiphilium, Acidocella and Acidobacterium-like isolates that grew in liquid cultures were able to reduce iron. In contrast, neither Acidisphaera rubrifaciens nor three Acidisphaera-like isolates tested were found to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(107 citation statements)
references
References 21 publications
1
103
0
3
Order By: Relevance
“…The labeled taxa in the oligotrophic peat included Holophagaceae and Anaeromyxobacter (Deltaproteobacteria) with members able to reduce HS analogue anthraquinone-2,6-disulfonate (AQDS) (72). None of the labeled taxa resembled known sulfate reducers but instead contained several potential Fe(III) reducers: Rhizomicrobium, Clostridia related to Clostridium saccharobutylicum, and Acidobacteria of groups 1 and 3 (73)(74)(75). Fermentative Fe(III) reducers have been shown to occur in an acidic fen (76).…”
Section: Discussionmentioning
confidence: 99%
“…The labeled taxa in the oligotrophic peat included Holophagaceae and Anaeromyxobacter (Deltaproteobacteria) with members able to reduce HS analogue anthraquinone-2,6-disulfonate (AQDS) (72). None of the labeled taxa resembled known sulfate reducers but instead contained several potential Fe(III) reducers: Rhizomicrobium, Clostridia related to Clostridium saccharobutylicum, and Acidobacteria of groups 1 and 3 (73)(74)(75). Fermentative Fe(III) reducers have been shown to occur in an acidic fen (76).…”
Section: Discussionmentioning
confidence: 99%
“…The changes in the microbial diversity of this effluent were mainly determined by analysis using an oxygen gradient. Within the mine portal, conditions are anoxic, so in the first section of the effluent the microorganisms involved in the various chemical reactions must be anaerobic (obligate or facultative) sulfur-and iron-reducing microorganisms (12,19). At the LZ1 station, the presence of oxygen generated by the photosynthetic biofilms, together with the atmospheric oxygen diffusing throughout the water column, favors the appearance of iron-and sulfur-oxidizing microorganisms ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, no PCR products of Anaeromyxobacter, or Shewanella related species were obtained from the lowland fen, although microorganisms from these genera are common to various metal-reducing environments. Recently it was shown that Acidobacterium capsulatum is capable of Fe(III) reduction in a pH range of 2 to 5 (Blöthe et al, 2008) and that the potential for dissimilatory Fe(III) reduction is widespread among acidophilic heterotrophic bacteria (Coupland and Johnson, 2008). Acidobacteria are present in peatlands (Dedysh et al, 2006) and have been detected also in the upland fen of this catchment (Schmalenberger et al, 2008).…”
Section: Fe(iii)-reducing Microbial Communities Of Acidic Habitatsmentioning
confidence: 97%